If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+-6+9+2X-19=23
We move all terms to the left:
X+-6+9+2X-19-(23)=0
determiningTheFunctionDomain X+2X-6+9-19-23+=0
We add all the numbers together, and all the variables
3X=0
X=0/3
X=0
| 8+5n=8n+2 | | 7x^2+5=1,377 | | 2÷3y+4=8 | | -4x+3x=2= | | -5(-2x+4)-1=12 | | 3x-15+7x=30 * | | -15+6=10y+16 | | 2x-8/3x=12 | | x*x^-1=7 | | f(-4)=3(-4)–14 | | 2y0+7y9−4y=0 | | 2(x^2+2)=56 | | 3x+5x=51 | | 3/15=x/45 | | x2+11x+22=0(x-3)(x-6) | | m=55-8.5(-2) | | 5=(2g+3) | | 0.5(4x+8)=2x+4 | | 5x+4(×-2)=100 | | 4.2g+6=2.2g+12 | | 5x=(8x+3) | | 5x+(4x-2)=100 | | 5(x+6)^=60 | | 11+3x+3=-1+2x | | √7^x=343 | | 7(x+2)-6(x-9)=22 | | y/4=-33 | | 4n+7=-2n+7 | | 13=4*a | | -33=-w/8 | | f=92f^2 | | (x+4)/2=14 |